2014
DOI: 10.1158/1055-9965.epi-14-0541
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Cancer Prevention Study II Nutrition Cohort Colorectal Tissue Repository

Abstract: Background: To better understand colorectal cancer etiology and prognosis, archived surgical tissues were collected from Cancer Prevention Study II (CPS-II) Nutrition Cohort participants who were diagnosed with colorectal cancer. Herein, the methodology for this collection is described to help inform other efforts to collect tissues.Methods: The main components to accruing tissue were: (i) obtaining consent from participants or next-ofkin; (ii) contacting hospitals to request materials; and (iii) pathology rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This rate compares favorably with the rate reported for the Cancer Prevention Study II Nutrition Cohort Colorectal Tissue Repository (43%) (12). The CPS II effort also reported a higher success rate (87%) for cases diagnosed within 10 years of the collection date than those diagnosed more than 10 years (32%).…”
Section: Discussionsupporting
confidence: 72%
“…This rate compares favorably with the rate reported for the Cancer Prevention Study II Nutrition Cohort Colorectal Tissue Repository (43%) (12). The CPS II effort also reported a higher success rate (87%) for cases diagnosed within 10 years of the collection date than those diagnosed more than 10 years (32%).…”
Section: Discussionsupporting
confidence: 72%
“…Immigration epidemiological studies have reported that after the residents in low-incidence countries moved to high-incidence regions, the morbidity of colorectal cancer increased rapidly [37], which primarily attributed to the changes of dietary habit and lifestyle [38]. Tea, as one of the most popular beverages consumed worldwide, has been widely investigated the effects on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we collected detailed information on potential confounders and had a high follow-up rate of the cohorts. Fourth, this study represents a unique integrative molecular pathological epidemiology [47-52] analysis of prediagnostic plasma vitamin D and immunity status in tumour tissue, which has enabled us to provide novel epidemiologic evidence on the potential role of vitamin D in cancer immunoprevention.…”
Section: Discussionmentioning
confidence: 99%